2015
DOI: 10.1007/s10509-015-2332-5
|View full text |Cite
|
Sign up to set email alerts
|

Dirac and scalar particles tunnelling from topological massive warped-AdS3 black hole

Abstract: This paper discusses the effects of the mass and the angular momentum of massive vector and scalar particles on the Hawking temperature manifested under the effects of the generalized uncertainty principle (GUP). In particular, we calculate the Hawking temperature of a black hole in a warped DGP gravity model in the framework of the quantum tunneling method. We use the modified Proca and Klein-Gordon equations previously determined from the GUP Lagrangian in the spacetime background of a warped Dvali-Gabadadze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…From these methods, the Hamilton-Jacobi method, based on quantum tunneling process of a particle, is the most popular method [17][18][19][20][21][22][23][24][25][26][27]. By using the Hamilton-Jacobi approach, Hawking radiations of a number of black holes as quantum tunneling process of a point particle have been investigated in the literature [28][29][30][31][32][33][34][35][36][37][38][39][40]. Recently, it has been also showed that Elko (dark) particles which are spin-1/2 fermions of mass dimension one and dual-helicity eigen spinors of the charge conjugation operator are emitted at the expected Hawking temperature from black holes and strings [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…From these methods, the Hamilton-Jacobi method, based on quantum tunneling process of a particle, is the most popular method [17][18][19][20][21][22][23][24][25][26][27]. By using the Hamilton-Jacobi approach, Hawking radiations of a number of black holes as quantum tunneling process of a point particle have been investigated in the literature [28][29][30][31][32][33][34][35][36][37][38][39][40]. Recently, it has been also showed that Elko (dark) particles which are spin-1/2 fermions of mass dimension one and dual-helicity eigen spinors of the charge conjugation operator are emitted at the expected Hawking temperature from black holes and strings [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, various methods have been proposed to calculate the temperature of a black hole known as Hawking temperature. On the other hand, the Hamilton-Jacobi approach is an important version of the tunnelling method of the quantum mechanical point-like particles from a black hole [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Adopting this approach, Hawking temperature of various black holes were recovered by quantum tunnelling method of the particles across their event horizons.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the NMG has non-trivial solutions, such as the Banados-Teitelboim-Zanelli (BTZ) black hole [6], Lifshitz black hole [7], the Warped-AdS 3 black hole [8], the New type black hole [9], de Sitter spacetime [10], AdS3 pp-wave [11,12], homogeneous anisotropic of Bianchi type-VI0, and type-VII0 [13]. On the other hand, the Hawking radiation of these black holes were investigated by the quantum mechanical tunnelling of the scalar, Dirac particles [14,15,17] and vector boson particles [16].…”
Section: Introductionmentioning
confidence: 99%